Manipulation of human mind through the power of discourse: a study on Bangladeshi call center conversations - Baidya, Tushar Kanti (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2016.